EVALUATIVE STUDY RELEVANCE OF CURRICULUM DEVELOPMENT MODEL OF ELEMENTARY SCHOOL TEACHER EDUCATION WITH ELEMENTARY SCHOOL CURRICULUM - Pangestu, Deviyanti (Universitas Islam Negeri Raden Intan Lampung, 2019)
The purpose of this study (1) to find out the relevance of the curriculum model development of Elementary School Teacher Education with the Elementary School curriculum, (2) to produce a level of improvement in courses that have relevance to the Elementary School curriculum, 3) produce textbooks. the method used in this study is Research and Development. Data collection used questionnaire. The results of the study showed that the average score of elementary school teacher's pedagogical competence was included in the excellent category as well as teacher professionalism. The average score was included in the excellent category. The pedagogical abilities and professional abilities of teachers in relation to the relevance of the Elementary School Teacher Education curriculum with the curriculum in Elementary Schools are related in the excellent categories.